Beyond the one best market: an essay on trans-economic exchange rates - Steffen Roth (ԲԱՆԲԵՐ. Bulletin of the Yerevan State University, 2010)
We routinely trust organizations that convert belief, truth, health, power, or beauty into money. Nonetheless, we know almost nothing about the corresponding exchange rates. Based on a system theorist concept of functional differentiation and the Bourdieueconomic forms of capitals, the paper presents strong evidence for the existence of non-economic markets for the mentioned values. The conclusion of the paper is that organizations with a more polyphonic, non-reductionist self- and market concept can act strategically as change agencies between those “markets of society”, i.e. they can influence the exchange rates between economic and non-economic values in terms of trans-political trade cycle politics.
Keywords: A14; Z13; 330; Market; Luhmann; Social Systems Theory; Polyphony; Functional Differentiation